1984
DOI: 10.1126/science.6719123
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain Lesions Disrupt Development But Not Maintenance of Song in Passerine Birds

Abstract: The magnocellular nucleus of the anterior neostriatum is a forebrain nucleus of passerine birds that accumulates testosterone and makes monosynaptic connections with other telencephalic nuclei that control song production in adult birds. Lesions in the magnocellular nucleus disrupted song development in juvenile male zebra finches but did not affect maintenance of stable song patterns by adult birds. These results represent an instance in which lesions of a discrete brain region during only a restricted phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
618
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 784 publications
(635 citation statements)
references
References 17 publications
15
618
2
Order By: Relevance
“…Converging evidence suggests that a component of song variability is actively introduced into the vocal motor pathway by neurons in a forebrain-basal ganglia circuit specialized for song, the anterior forebrain pathway (AFP) (Bottjer et al 1984;Hessler and Doupe 1999;Kao and Brainard 2006;Kao et al 2005;Ö lveczky et al 2005;Scharff and Nottebohm 1991). In particular, the lateral nucleus of the nidopallium (LMAN), which projects to the robust nucleus of the arcopallium (RA) in the vocal motor pathway, has been found to influence vocal motor variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Converging evidence suggests that a component of song variability is actively introduced into the vocal motor pathway by neurons in a forebrain-basal ganglia circuit specialized for song, the anterior forebrain pathway (AFP) (Bottjer et al 1984;Hessler and Doupe 1999;Kao and Brainard 2006;Kao et al 2005;Ö lveczky et al 2005;Scharff and Nottebohm 1991). In particular, the lateral nucleus of the nidopallium (LMAN), which projects to the robust nucleus of the arcopallium (RA) in the vocal motor pathway, has been found to influence vocal motor variability.…”
Section: Discussionmentioning
confidence: 99%
“…C: average fundamental frequency (FF) during FD songs produced in the 1st minute following the introduction of the female was elevated relative to FF for UD songs produced during the preceding 2 min. Plotted are the average FFs during these periods, divided by the average values across all UD songs for each male, for 3 syllables that showed significant changes inlable structure and sequencing (Bottjer et al 1984;Kao et al 2005;Ö lveczky et al 2005;Scharff and Nottebohm 1991). Furthermore, the variability of spiking activity in LMAN is reduced during renditions of FD song, which could serve to reduce the variability of firing in RA and, consequently, syllable structure (Hessler and Doupe 1999;Kao et al 2005;Leonardo and Fee 2005;Ö lveczky et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any MAN fibers traveling by HVC on way to RA could have been affected. However, Bottjer et al (1984) have shown that lesions of MAN in adult zebra finches have no effect on song syllables. A representative section from the male with the smallest lesion is shown in Figure 5B.…”
Section: Efects Of H Vc Lesionsmentioning
confidence: 97%
“…To address this issue, we altered the firing pattern of RA neurons without the possibility of concurrently activating HVc by stimulating the second major input to RA, the lateral magnocellular nucleus of the anterior neostriatum (L-MAN). Although L-MAN is not critical for adult song production (Bottjer et al, 1984), electrical stim- ulation of L-MAN in vivo evokes bursts of multiunit activity in RA (Williams, 1989) and stimulating its fibers in brain slices evokes sizable excitatory postsynaptic potentials in RA neurons (Kubota and Saito, 199 1;Mooney and Konishi, 199 1;Mooney, 1992). Thus, strongly stimulating L-MAN during singing should distort the firing pattern of many RA neurons.…”
Section: Antidromic Activation Of Hvc Alters Syllable Sequencingmentioning
confidence: 99%